E-Konsulta: Clinic Medical Record Management System with Online Follow-Up Through Google Meet: Author's Country: Pagadian City, Philippines (Information System; Universitas Buana Perjuangan Karawang, 2025)
An operational clinic is essential in educational institutions to support the health and well-being of students and staff, directly enhancing productivity and academic achievement. However, many clinics still rely on outdated, paper-based systems, leading to inefficiencies, delays, and errors. Modernizing healthcare through digital solutions can improve efficiency, accuracy, and accessibility. This study proposed a system application to address common issues by digitizing medical records, automating workflows, and enabling online consultations. The platform enhances the accuracy and accessibility of patient data while streamlining administrative tasks, benefiting all stakeholders. Extensive testing revealed excellent performance, with a 100% pass rate in most functional areas and high scores in non-functional aspects, including reliability (97.14%), security (95.71%), and user experience (98.57%). Minor areas for improvement were noted in certain functionalities (92.90%) and accessibility (90%), underscoring the importance of continuous optimization to enhance inclusivity and usability. Future enhancements could include developing a mobile application for improved accessibility, enabling users to access records, book appointments, and participate in consultations on their devices. Advanced features such as enhanced online follow-up consultations, automated reminders, and health monitoring tools could further improve healthcare delivery. Integrating real-time analytics or telehealth capabilities may also provide broader support for patient care. These recommendations highlight the potential for the system to evolve, offering a more efficient, inclusive, and responsive approach to healthcare within educational environments